ZnO core–shell microspheres prepared by one‐pot hydrothermal reaction and their photocatalysis properties. (1st May 2014) - Liu, Yingying; Jia, Xiaohua; Wu, Xiangyang
Abstract : ZnO core–shell microspheres were fabricated by a facile one‐pot hydrothermal method without any other surfactant or template. The structure, morphologies and properties of the as‐prepared samples were determined using X‐ray diffraction, scanning electron microscopy and ultraviolet (UV) and visible absorption spectroscopy. Results showed that the zinc ions were first adsorbed onto the surface of a sucrose droplet or included in the droplet and then reacted with each other to form a ZnO crystal nucleus, which was followed by the growth and calcination steps to form ZnO core–shell microspheres. The photocatalytic characterisation revealed that ZnO core–shell microspheres behave high photocatalytic activity for methylene blue under UV light irradiation, and the degradation rate can reach to 97.64% in 210 min.